2013
DOI: 10.1111/jhn.12153
|View full text |Cite
|
Sign up to set email alerts
|

Meeting challenges related to the dietary assessment of ethnic minority populations

Abstract: From the results of in-house studies and a revision of practices reported in earlier literature, two 24-h face-to-face dietary recalls are recommended as the optimal method for the dietary assessment of migrant South Asians. To complement this assessment, ethnic-specific food frequency questionnaires such as that developed and successfully implemented among South Asians in the present study must be employed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 31 publications
(26 reference statements)
0
20
0
Order By: Relevance
“…These included household utensils, 33 , 51 , 66 previously validated by Edington et al, 81 and food atlas photos, 38 previously validated by Nelson et al, 10 but the validation had been done in native (rather than ethnic minority) populations. This also applied to other PSEEs, such as those used in the Oslo Immigrant Health Study questionnaire 41 and the dietary habits survey used by Sun et al 30 (details in Tables S2 and S4 of the Supporting Information online, including original and follow-up data for 4 PSEEs 51 , 52 , 82 , 83 ).
Figure 4 Quality measures reported across the 42 studies examined in this review .
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These included household utensils, 33 , 51 , 66 previously validated by Edington et al, 81 and food atlas photos, 38 previously validated by Nelson et al, 10 but the validation had been done in native (rather than ethnic minority) populations. This also applied to other PSEEs, such as those used in the Oslo Immigrant Health Study questionnaire 41 and the dietary habits survey used by Sun et al 30 (details in Tables S2 and S4 of the Supporting Information online, including original and follow-up data for 4 PSEEs 51 , 52 , 82 , 83 ).
Figure 4 Quality measures reported across the 42 studies examined in this review .
…”
Section: Resultsmentioning
confidence: 99%
“…Beyond the lack of absolute or relative measures of validity, reliability, or feasibility of some PSEEs 28 , 29 , 42 , 43 , 54 , 58 , 62 , 63 , 77 , 79 or the only partial validation of other PSEEs, 33 , 41 , 53 , 59 , 66 , 68 , 83 other limitations included the following: low sensitivity of the tool due to a small number of portion options or photos 11 , 17 , 25 , 26 , 29 , 32 , 40 , 43 , 52 , 55 , 65 ; grouping of mixed dishes and omission of food items in questionnaires 27 , 35 , 42 ; lack of breadth 28 ; requirement for high level of staff training or involvement 33 , 37 , 64 , 68 ; requirement for participants to be literate or skilled in operating equipment 33 , 37 or in performing numerical calculations 30 ; requirement for participants to possess specific technology 29 ; long time elapsed between dietary assessment with the new PSEE and the comparison method (which effectively means the 2 methods were comparing different things), or long time elapsed between test and re-test evaluations 26 , 38 , 40 ; and testing of PSEE in only one gender or age group 17 , 25 , 30–32 , 36–38 , 55 , 56 , 61 , 63 , 64 , 83 , 79 . Other issues were validation conducted in nonminority ethnic group populations 30 , 41 ; low retention rates 41 , 43 ; study not powered to detect ethnic subgroup differences 29 or validity/reliability 38 , …”
Section: Resultsmentioning
confidence: 99%
“…5---8 Furthermore, children of various Asian and Latino ethnic groups with distinct historical, migration, and social contexts are generally grouped together in research analyses, making it difficult to understand the ethnicity-specific salient roles that education, income, and acculturation may play in specific dietary practices. 9,10 Acculturation has been described as both a protective factor and a risk factor for healthy dietary practices among immigrants. For example, acculturation among Latinos has been associated with higher consumption of fruits and vegetables but also with higher rates of fast food and sugary food consumption in both pediatric and adult Latino populations.…”
mentioning
confidence: 99%
“…A review by Burrows et al has indicated that weighed food records may provide the best dietary estimates for younger children from 0.5 to 4 years old [41]. However, the 24-h multiple-pass recall is less time consuming and is reportedly used more frequently among immigrant populations, along with FFQs [39,42]. The recalls were mainly performed face-to-face, which may be a benefit as potential misunderstandings can be easily clarified in a personal interview.…”
Section: Discussionmentioning
confidence: 99%